Active uptake of dendritic cell-derived exovesicles by epithelial cells induces the release of inflammatory mediators through a TNF-alpha-mediated pathway - Obregon, Carolina; Rothen-Rutishauser, Barbara; Gerber, Peter; Gehr, Peter; Nicod, Laurent P (The American journal of pathology, 2009)
Dendritic cells (DCs) can release hundreds of membrane vesicles, called exovesicles, which are able to activate resting DCs and distribute antigen. Here, we examined the role of mature DC-derived exovesicles in innate and adaptive immunity, in particular their capacity to activate epithelial cells. Our analysis of exovesicle contents showed that exovesicles contain major histocompatibility complex-II, CD40, and CD83 molecules in addition to tumor necrosis factor (TNF) receptors, TNFRI and TNFRII, and are important carriers of TNF-alpha. These exovesicles are rapidly internalized by epithelial cells, inducing the release of cytokines and chemokines, but do not transfer an alloantigen-presenting capacity to epithelial cells. Part of this activation appears to involve the TNF-alpha-mediated pathway, highlighting the key role of DC-derived exovesicles, not only in adaptive immunity, but also in innate immunity by triggering innate immune responses and activating neighboring epithelial cells to release cytokines and chemokines, thereby amplifying the magnitude of the innate immune response.